2020
DOI: 10.1109/access.2020.3009244
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Fusion Approach for Hate Speech Detection

Abstract: In recent years, the increasing prevalence of hate speech in social media has been considered as a serious problem worldwide. Many governments and organizations have made significant investment in hate speech detection techniques, which have also attracted the attention of the scientific community. Although plenty of literature focusing on this issue is available, it remains difficult to assess the performances of each proposed method, as each has its own advantages and disadvantages. A general way to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 22 publications
(25 reference statements)
0
22
0
1
Order By: Relevance
“…We shall mention the merits of the recently introduced ELMO word embedding model, which was designed to overcome the aforementioned shortcoming. A recent work by Zhou et al [161] using ELMO embedding showed a better performance compared to CNN. However, since ELMO is a relatively new, the in-depth comparison with other embedding model is still in its infancy.…”
Section: Overview Of Deep-learning Recordsmentioning
confidence: 94%
“…We shall mention the merits of the recently introduced ELMO word embedding model, which was designed to overcome the aforementioned shortcoming. A recent work by Zhou et al [161] using ELMO embedding showed a better performance compared to CNN. However, since ELMO is a relatively new, the in-depth comparison with other embedding model is still in its infancy.…”
Section: Overview Of Deep-learning Recordsmentioning
confidence: 94%
“…More recently, many works [21,22,23,34,24,25,26,27] remarking that in [20,23], LR obtained very competitive rates compared to the proposals.…”
Section: Ensemble For Hate Speech Detectionmentioning
confidence: 99%
“…Based on Table 1, we can see that more and more research works are considering an ensemble model to improve hate speech detection [24,26,23,19,17]. Some works generate an ensemble by just changing the classification model [17] employed, while others consider a homogeneous ensemble trained with different input features [25,24]. Furthermore, multiple works only consider features from the same families such as [25,24,28] which are only based on language models like BERT and other variations.…”
Section: Literature Gapmentioning
confidence: 99%
“…Yapılan incelemeler sonucunda NS tespiti için derin öğrenme yaklaşımları ile yapılan çalışmalarda literatürde yer almaktadır [18][19][20][21]. Tripathy ve arkadaşları Derin Evrişimli Sinir Ağı (DCNN) kullanılarak otomatik bir NS tespit sistemi geliştirilmiştir.…”
Section: İlgili çAlışmalarunclassified